Programmed cell death ligand 1 expression in a case of poorly differentiated lymphocyte‐rich hepatocellular carcinoma. Issue 9 (9th September 2021) - Omori, Ginji; Osuga, Takahiro; Miyanishi, Koji; Hamaguchi, Kota; Tanaka, Shingo; Ohnuma, Hiroyuki; Murase, Kazuyuki; Takada, Kohichi; Nagayama, Minoru; Kimura, Yasutoshi; Takemasa, Ichiro; Kikuchi, Yasuhiro; et al.
Abstract: Our pathological study of a case of poorly differentiated lymphocyte‐rich hepatocellular carcinoma suggested that immune checkpoint inhibitor may be an effective therapy. The histological type is an important factor in determining treatment choices. Abstract : We presented a rare case of poorly differentiated lymphocyte‐rich hepatocellular carcinoma. In this case, multiple small foci of programmed cell death ligand 1 positive inflammatory cell clusters were founded around glypican 3‐positive tumor cells.